AUTHOR, READER, NARRATOR. THE PERMEABILITY OF THE BOUNDARIES IN MICHAL AJVAZ'S TEXTS - Jurajdová, Zuzana (Bohemica Olomucensia, 2021)
If one accepts the permeability of the boundaries between reality and fiction, then it is necessary to admit such a changeability also in case of the participants in the process of literary output and its reception. This paper deals with the dynamics between these participants and text itself in works of Michal Ajvaz.
Keywords: Michal Ajvaz; reality; fiction; author; reader; narrator